Pengembangan Perangkat Pembelajaran Matematika Berbasis Masalah (PBM) Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VII SMP - Suri Srima Eled; Hendra Syarifuddin; Edwin Musdi (JEMS: Jurnal Edukasi Matematika dan Sains, 2021)
Mathematical problem solving ability is expected to develop well in each student. However, the reality is that students' mathematical problem solving abilities are still not optimal and have not been facilitated to develop these abilities properly. Based on this, it is necessary to develop learning tools based on problem based learning to improve students' problem solving abilities. The research was conducted with the aim of knowing the characteristics of problem based learning-based learning devices that are valid, practical and effective to improve the mathematical problem solving abilities of students in class VII SMP. This type of research is development research using the Plomp model, which consists of three stages, namely the preliminary stage, the prototype-making stage and the assessment stage. The tools made are problem based learning-based lesson plans and worksheets for class VII SMP. The instruments used are validation sheets, observation sheets, questionnaires, interviews and tests. The results showed that the learning tools in the form of lesson plans and LKPD based on problem based learningfor class VII SMP were valid and practical. The validity of the RPP reached 79.5 % and LKPD 82,5%. While the practicality of the lesson plans is 81.35% and LKPD 83.5%. Based on this, it can be concluded that problem based learning-based learning tools for class VII SMP with material Sets in semester 1 are valid, practical and effective and can be used as input materials in the mathematics learning process.